Major CD4 T-Cell Depletion and Immune Senescence in a Patient with Chronic Granulomatous Disease - Albuquerque, Adriana S.; Fernandes, Susana M.; Tendeiro, Rita; Cheynier, Rémi; Lucas, Margarida; Silva, Susana L.; Victorino, Rui M. M.; Sousa, Ana E. (Frontiers in Immunology, 2017)
Chronic Granulomatous Disease (CGD) results from primary defects in phagocytic reactive oxygen species (ROS) production. T-cell evaluation is usually neglected during patients’ follow-up, although T-cell depletion has been reported in CGD through unknown mechanisms. We describe here a 36-year-old patient with X-linked CGD with severe CD4 T-cell depletion below 200 CD4 T-cells/l, providing insights into the mechanisms that underlie T-cell loss in the context of oxidative burst defects. In addition to the typical infections, the patient featured a progressive T-cell loss associated with persistent lymphocyte activation, expansion of IL-17-producing CD4 T-cells, and impaired thymic activity leading to a reduced replenishment of the T-cell pool. A relative CD4 depletion was also found at the gut mucosal level, though no bias to IL-17-production was documented. This immunological pattern of exhaustion of immune resources favors prompt, potentially curative, therapeutic interventions in CGD patients, namely stem-cell transplantation or gene therapy. Moreover, this clinical case raises new research questions on the interplay of ROS production and T-cell homeostasis and immune senescence.